Occupational groups prediction in Turkish Twitter data by using machine learning algorithms with multinomial approach - YILDIZ, KAZIM (My University, 2024)
A lot of research has been done on personality and sentiment analysis, demographic and professional aspects using user shares in social networks. In particular, information extraction and value are produced based on Twitter data. This study aims to predict the users, occupational groups, who share in Turkish on Twitter, using machine learning methods. First, occupational groups and the Twitter accounts of the occupations in these occupational groups were determined manually and the tweets shared in these accounts were scraped. All tweets were then grouped by occupation into groups of one, five and ten, creating datasets with different characteristics, each containing more than 500,000 tweets. Some datasets were preprocessed using the Zemberek library, which is used in many Turkish NLP studies, and experiments were conducted out with a total 6 datasets. During the preprocessing phase, since the ready-made stopwords lists were not considered sufficient, unnecessary word lists consisting of single and binary words were created manually. Count and TF-IDF vectorizers are used to convert textual data into numerical. Since each word represents a variable in the text classification study, new variables were created by combining double and triple word phrases (ngrams) with feature extraction. In the experiments in which 24 different models were run, instead of using all the features created, the method of \"determining the optimal number of features\", which consists of the most valuable features, was used. It was found that the most successful model in the experiments using machine learning algorithms with a multinomial approach achieved 97.3% success in all calculated metrics.
Keywords: Bilgisayar Bilimleri; Algoritmalar; Mühendislik ve Teknoloji; Computer Sciences; algorithms; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; Mühendislik; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; ENGINEERING; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; Genel Mühendislik; Fizik Bilimleri; Bilgisayar Bilimi Uygulamaları; Yapay Zeka; General Engineering; Physical Sciences; Computer Science Applications; Artificial Intelligence; Data mining; Machine learning; Multinomial approach; Occupation prediction; Turkish twitter data analysis